Oxidative stress and plasma ceramides in broiler chickens - Klandorf, Hillar; Dartigue, Vincent (Frontiers in Physiology, 2024)
The selection for rapid growth in chickens has rendered meat-type (broiler) chickens susceptible to develop metabolic syndrome and thus inflammation. The sphingolipid ceramide has been linked as a marker of oxidative stress in mammals, however, the relationship between sphingolipid ceramide supply and oxidative stress in broiler chickens has not been investigated. Therefore, we employed a lipidomic approach to investigate the changes in circulating sphingolipid ceramides in context of allopurinol-induced oxidative stress in birds. Day zero hatched chicks (n=60) were equally divided into six groups; an unsupplemented control, an allopurinol group (25mg/kg body weight), a conjugated linoleic acid (CLA) group where half of the oil used in the control diet was substituted for a CLA oil mixture, a CLA and an allopurinol group utilizing the same dose of CLA and allopurinol, a berberine (BRB) group consisting of berberine supplementation (200mg/Kg feed), and a BRB and allopurinol group, utilizing the same dose of BRB and allopurinol. Conjugated linoleic acid and berberine were utilized to potentially enhance antioxidant activity and suppress the oxidative stress induced by allopurinol treatment. Body weight, plasma uric acid, nonesterified fatty acids (NEFA) and sphingolipid ceramides were quantified. Allopurinol induced an inflammatory state as measured by a significant reduction in plasma uric acid -an antioxidant in birds as well as a metabolic waste product. Results showed that both total and saturated sphingolipid ceramides declined (P < 0.05) with age in unsupplemented chicks, although plasma ceramides C16:0 and 18:0 increased in concentration over the study period. Simple total and saturated sphingolipid ceremide's were further decreased (P < 0.05) with allopurinol supplementation, however, this may be an indirect consequence of inducing an inflammatory state. Neither CLA or BRB were able to significantly attenuate the decline. The administration of allopurinol specifically targets the liver which in birds, is the primary organ for fatty acids synthesis. For this reason, sphingolipid ceramide production might have been unwittingly affected by the addition of allopurinol.